2007
DOI: 10.1590/s0102-05362007000300006
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de híbridos duplos de pimentão

Abstract: Obteve-se híbridos duplos de pimentão, os quais foram avaliados por estimativa da heterose em relação à média dos progenitores, ao progenitor superior e ao híbrido padrão. Dez híbridos duplos foram obtidos em casa de vegetação a partir de cruzamentos entre cinco híbridos simples, Magali R (híbrido padrão), BGJ-27, BGJ-28, BGJ-29 e BGJ-30. O delineamento experimental adotado foi de blocos casualizados, com três repetições e 15 tratamentos, sendo cinco híbridos simples e dez híbridos duplos. Foram avaliados o nú… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 2 publications
1
10
0
10
Order By: Relevance
“…PTH has direct influence on mass and post-harvest conservation of Capsicum fruit, i.e., is linked to fruit yield and quality (Blat et al, 2007). For such trait, hybrids were differentiated into two groups in both environments.…”
Section: Resultsmentioning
confidence: 99%
“…PTH has direct influence on mass and post-harvest conservation of Capsicum fruit, i.e., is linked to fruit yield and quality (Blat et al, 2007). For such trait, hybrids were differentiated into two groups in both environments.…”
Section: Resultsmentioning
confidence: 99%
“…Such reductions are desirable for ornamental Capsicum breeding programs. Additionally, Blat et al (2007), conducting studies in pepper hybrids with basis on heterosis estimation, found negative heterosis for plant height and according to these authors, medium heights are ideal for pepper plants. However, for ornamental purposes, small-sized plants are preferred for pot cultivation.…”
Section: Scott-knott Grouping Test Of Averagesmentioning
confidence: 94%
“…Values of negative heterosis for height indicate smaller plants, ideal for pot cultivation. Nascimento et al (2010) (Blat et al, 2007;Patil & Bhalekar, 2012;Silva et al, 2015). Gomide et al (2003) and Patil & Bhalekar (2012) achieved negative heterosis (-4.50 to -75.76) and (-1.31 to -17.61) for earliness in peppers and chilies (Capsicum annuum), respectively.…”
Section: Scott-knott Grouping Test Of Averagesmentioning
confidence: 99%
“…The experiment consisted in 30 lots with seven plants each; on 15 of these lots, the thinning of stems was performed starting from the third bifurcation, leaving them with four main stems (Factor et al, 2008;Charlo et al, 2009). In all lots, under the first bifurcation, sprout thinning was performed when necessary, and flowers were removed from the first bifurcation (Blat et al, 2007). Volunteer plants control was performed by manual weeding; on the other hand, pest control, according to the organic production, occurred when needed, in accordance with Normative Ruling n. 46, issued by MAPA (Brasil, 2011).…”
Section: Methodsmentioning
confidence: 99%